THE MANIFESTATION OF COMMUNICATIVE, PRAGMATIC FEATURES OF SPEECH ETIQUETTE IN THE DIALOGUES OF RUSSIAN, ENGLISH CULTURAL CARRIERS - Khusainova, Zebo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article informs about the communicative linguistics in various cultures, the provisions which includes the theory of intercultural communication. The farewell, and greetings in speech etiquette situations in the following linguistic cultures, Russian and English are given as an integral part, the pragmatic features of the normative politeness in these languages also, the dialogue among the communicators in those ethnocultural linguistics, and the usage of politeness in it are investigated. Thus, the cultural awareness that manifests in the communication by Russian and English as well as its reflection to complicated acts of etiquette communication are informed too.